PERSEPSI DAN SIKAP AFEKTIF MEMPENGARUHI PERILAKU IBU MENYEDIAKAN IKAN LAUT DALAM MENU KELUARGA - Waysima, Waysima; Sumarwan, Ujang; Khomsan, Ali; Zakaria, Fransiska R (Jurnal Ilmu Keluarga dan Konsumen, 2011)
The aim of this research was to analyze determinant factors of mother’s behavior to provide sea fish in family menu. The study was conducted in coastal and noncoastal areas of Central Java. The participants were 248 mothers of fifth and sixth grade elementary students that were selected by clustered random sampling. Data collected by interview with questionnaires. Data was analyzed by descriptive, Independent Sample T Test, regression, and path analysis. Family size, mother’s education, income per capita per month, and expenditure allocation of fish were significant different between family in coastal and noncoastal areas. Meanwhile, mother’s perception, affective attitude, and behavior to provide sea fish in family menu also significant different between family in coastal and noncoastal areas. The results showed that mother’s behavior of fish availability in family menu was influenced by mother’s perception, mother’s affective attitude, location of residence, income per capita per month, and mother’s education.